Corticoid Injection for Subacromial Impingement Syndrome Treatment - Huu, Manh Nguyen; Trung, Dung Tran; Ngoc, Thanh Ma; Tran, Quyet; Khanh, Trinh Le; My, Hanh Tran Thi; Tien, Dat Tran (Global Journal of Medical and Clinical Case Reports, 2017)
Objective: Evaluate the treatment result of corticoid injection for subacromial impingement syndrome Patients and method: 30 patients with shoulder pain for at least 3 months, diagnosed subacromial impingement syndrome, excluded rotator cuff tear and labral lesion. A single injection into subacromial space with Methylprednisolone acetate 40 mg. Evaluate the result with VAS and Constant score. Results: Pre-injection average VAS is 8,4 ± 1, 25; Post-injection VAS is 2,6 ± 1,12; Pre-injection average Constant score is 44,1 ± 9,32. Post-injection average Constant score is 61,2 ± 10,34. The difference between pre-injection and post-injection results is significant with p < 0,05. Conclusion: Corticoid to subacromial space results in improving symptoms of pain and functional shoulder joint.